The Office for National Statistics Longitudinal Study of England and Wales: the research possibilities of its large sample size and the 2021 Census linkage - Sizer, Alison (International Journal of Population Data Science, 2025)
Objectives The Office for National Statistics Longitudinal Study (ONS-LS) is a complex longitudinal dataset including data from the 1971 – 2011 decennial censuses with linked administrative data on births, deaths and cancer registrations. It is representative of the England and Wales population and will soon be linked to the 2021 Census data. Methods The ONS-LS was set up in 1974 to address the limitations of the occupational data collected at death registration used to calculate occupational mortality rates, and a need for more information on fertility patterns, particularly changes in birth spacing. The initial sample was drawn from the 1971 Census based on four confidential birthdays to facilitate linkage, giving a representative sample amounting to just over 1% of the population of England and Wales. The study has been maintained as a continuous multi-cohort through the addition of new births and immigrants with the same birth date. Results The upcoming linkage of the 2021 Census will extend the study’s span to 50 years (1971-2021), and introduces several new questions, alongside questions asked for the second time. These offer opportunities for research on gender identity, sexuality and veteran status, and longitudinal transitions related to national identity and passports held. The 2021 Census also enables the examination of changes occurring in the 2011-2021 intercensal period, which saw Brexit and the covid-19 pandemic. The 2021 Census linkage is in its beta testing phase. We will present preliminary findings from our beta test project investigating whether “Brexit” was associated with changes in migration flows of EU nationals to/from England and Wales, and the extent to which it was associated with British citizens accessing EU member passports. Conclusions The ONS-LS is a vital research asset, providing access to a large sample of census data linked across six censuses, and strengthened through linkage to events data. As part of the wider UK Census Longitudinal Studies, the ONS-LS aligns with the Northern Ireland and the Scottish Longitudinal Studies, facilitating cross-UK analysis.